Necessidades atuais para a educação ambiental: serão possibilidades? - Chaddad, Flávio Roberto; Ghilardi, Renato Pirani [UNESP] (My University, 2010)
This study had two objectives: to build theoretically the hypothetical landmarks of the environmental crisis and to conjecture new horizons or utopias which can fulfill themselves in the future in search of another being of the man in the world. Therefore, a bibliographic research has been done and, as methodology of analysis, a dialectic critical method has been used to understand the reality in its contradictions and in the totality of the history, through some suggestions, going toward the domain of the state of things which we can verify in the world nowadays. It has been observed that the hypothetical landmarks of the environmental crisis had and have its origins in the Jewish-Christian monotheism, in the exacerbation of the reason as the only way of knowledge and in the process of capitalist accumulation. Therefore, these landmarks, in almost their totality, have historically been built even before the advent of the capitalism. From this point, three suggestions were launched as questions, or so, possibilities, to open a discussion about the construction of another paradigm: Is it necessary another sense of religion? Is it necessary another sense of reason? Is it necessary another sense of sustainable development? Thus, these questions which have been launched, were thought as the current necessities for the environmental education and they implicate in another historical condition to the mankind.

Este estudo teve dois objetivos: construir teoricamente os marcos hipotéticos da crise ambiental e vislumbrar novos horizontes ou utopias que possam se realizar futuramente em busca de um outro estar do homem no mundo. Foi realizada uma pesquisa bibliográfica e, como metodologia de análise, utilizou-se o método crítico dialético para entender a realidade em suas contradições e na totalidade da história, indo em direção, através de algumas sugestões, da superação para o estado de coisas que hoje verificamos no mundo. Notou-se que estes marcos tiveram e têm as suas origens no monoteísmo judaico-cristão; na exacerbação da razão como única forma de conhecer e no processo de acumulação capitalista. A partir disto, lançou-se três sugestões como questionamentos para abrir uma discussão a respeito da construção de um outro paradigma: É necessário um outro sentido de religião? É necessário um outro sentido de razão? É necessário um outro sentido de desenvolvimento sustentável? Desta maneira, estes questionamentos foram tidos como as necessidades atuais para a educação ambiental e implicam em uma outra condição histórica para a humanidade.
Keywords: Environmental education; Conception of environment; Environmental crisis; Reason and environment; Jewish-Christian monotheism and environment; Educação ambiental; Razão e meio ambiente; Monoteísmo judaico-cristão e meio ambiente; Capitalismo e meio ambiente